2021
DOI: 10.1021/acs.iecr.1c00927
|View full text |Cite
|
Sign up to set email alerts
|

Selective Aerobic Oxidation of Toluene in the Presence of Co2+ and Task-Specific Organic Salts, Including Ionic Liquids

Abstract: This paper presents research on the catalytic activity of systems composed of transition-metal compounds and organic bromide salts, [X][Br] or [X][Br 3 ], in the oxidation of toluene and its derivatives with oxygen using acetic acid as a solvent. Salts containing imidazolium, tetraalkylammonium, bromoalkylammonium, phenylalkylammonium, or benzylalkylammonium cations in combination with Co 2+ compounds were used. It was found that the [X][Br] and [X][Br 3 ] systems with Co 2+ compounds enabled the oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…As org bromides, bromide quaternary ammonium salts, phosphonium salts, and 1-butyl-3thylimidazolium bromide were used. As our previous studies [44] have shown, qua nary ammonium salts exhibit corrosion-inhibiting properties, which are a significant vantage when using organic bromides as catalysts in the oxidation of alkyl aromatic drocarbons. The composition of 3-picoline oxidation products was compared to a num of organic bromides, and the influence of basic parameters (temperature, time, press type of oxidizing agent) was examined for those selected.…”
Section: Introductionmentioning
confidence: 81%
“…As org bromides, bromide quaternary ammonium salts, phosphonium salts, and 1-butyl-3thylimidazolium bromide were used. As our previous studies [44] have shown, qua nary ammonium salts exhibit corrosion-inhibiting properties, which are a significant vantage when using organic bromides as catalysts in the oxidation of alkyl aromatic drocarbons. The composition of 3-picoline oxidation products was compared to a num of organic bromides, and the influence of basic parameters (temperature, time, press type of oxidizing agent) was examined for those selected.…”
Section: Introductionmentioning
confidence: 81%
“…The use of air as an oxidizing agent and the high yields and conversions are the advantages of this method. However, the high corrosivity of the Co/Mn/Br catalytic system and resulting need to use an appropriate construction material or corrosion inhibitors should be taken into account [88].…”
Section: Discussionmentioning
confidence: 99%
“…At present, benzoic acid is mainly prepared by liquid-phase air oxidation of toluene in industry, which generally uses transition metal salts (such as Co, Mn) as catalysts under a temperature of 150-170 °C and pressure of 8-10 MPa. [4] This method shows a high product yield for 80 %-90 %. However, the harsh reaction conditions lead to excessive energy consumption.…”
Section: Introductionmentioning
confidence: 97%
“…The demand for benzoic acid in the world is increasing every year, and the synthesis method of benzoic acid has attracted extensive attention of researchers. At present, benzoic acid is mainly prepared by liquid‐phase air oxidation of toluene in industry, which generally uses transition metal salts (such as Co, Mn) as catalysts under a temperature of 150–170 °C and pressure of 8–10 MPa [4] . This method shows a high product yield for 80 %–90 %.…”
Section: Introductionmentioning
confidence: 99%